Specialized pro-resolving lipid mediators regulate inflammatory macrophages: A paradigm shift from antibiotics to immunotherapy for mitigating COVID-19 pandemic - Kumar, Vikram; Yasmeen, Nusrath; Chaudhary, Anis Ahmad; Alawam, Abdullah S.; Al-Zharani, Mohammed; Suliman Basher, Nosiba; Harikrishnan, S.; Goud, Muddapuram Deeksha; Pandey, Aishwarya; Lakhawat, Sudarshan Singh; Sharma, Pushpender Kumar (Frontiers in Molecular Biosciences, 2023)
The most severe clinical manifestations of the horrifying COVID-19 disease, that claimed millions of lives during the pandemic time, were Acute respiratory distress syndrome (ARDS), Coagulopathies, septic shock leading eventually to death. ARDS was a consequence of Cytokine storm. The viral SARS-COV2infection lead to avalanche of cytokines and eicosanoids causing “cytokine storm” and “eicosanoid storm.” Cytokine storm is one of the macrophage-derived inflammatory responses triggered by binding of virus particles to ACE2 receptors of alveolar macrophages, arise mainly due to over production of various pro-inflammatory mediators like cytokines, e.g., interleukin (IL)-1, IL-2, and tumor necrosis factor (TNF)- α, causing pulmonary edema, acute respiratory distress, and multi-organ failure. Cytokine storm was regarded as the predictor of severity of the disease and was deemed one of the causes of the high mortality rates due to the COVID-19. The basis of cytokine storm is imbalanced switching between an inflammation increasing - pro-inflammatory (M1) and an inflammation regulating-anti-inflammatory (M2) forms of alveolar macrophages which further deteriorates if opportunistic secondary bacterial infections prevail in the lungs. Lack of sufficient knowledge regarding the virus and its influence on co-morbidities, clinical treatment of the diseases included exorbitant use of antibiotics to mitigate secondary bacterial infections, which led to the unwarranted development of multidrug resistance (MDR) among the population across the globe. Antimicrobial resistance (AMR) needs to be addressed from various perspectives as it may deprive future generations of the basic health immunity. Specialized pro-resolving mediators (SPMs) are generated from the stereoselective enzymatic conversions of essential fatty acids that serve as immune resolvents in controlling acute inflammatory responses. SPMs facilitate the clearance of injured tissue and cell debris, the removal of pathogens, and augment the concentration of anti-inflammatory lipid mediators. The SPMs, e.g., lipoxins, protectins, and resolvins have been implicated in exerting inhibitory influence on with cytokine storm. Experimental evidence suggests that SPMS lower antibiotic requirement. Therefore, in this review potential roles of SPMs in enhancing macrophage polarization, triggering immunological functions, hastening inflammation resolution, subsiding cytokine storm and decreasing antibiotic requirement that can reduce AMR load are discussed.